Biological monitoring as a valid tool to assess occupational exposure to mixtures of 2,4-:2,6-toluene diisocyanate / Validità del monitoraggio biologico per la valutazione dell’esposizione professionale a miscele di 2,4-:2,6-toluendiisocianato - De Palma, Giuseppe; Cortesi, Ilenia; Ghitti, Roberta; Festa, Denise; Bergonzi, Roberto; Apostoli, Pietro (La Medicina del Lavoro, 2012)
SummaryBackground and Objectives: Despite its advantages over environmental monitoring, biological monitoring of exposure to 2,4-:2,6-toluene diisocyanate (TDI) mixtures is still underused. The present study was designed in order to evaluate the feasibility and reliability of biological monitoring in a factory producing polyurethane foam blocks. Methods: Airborne TDI isomers were sampled by both static and personal pumps and determined by HPLC with fluorimetric detection. Specific metabolites 2,4- and 2,6-toluenediamine (TDA) were determined by gas chromatography-mass spectrometry on hydrolysed  urine samples collected from 16 workers at the beginning of the workweek and both before (BS) and at the end (ES) of the 4th workday. Additional samples were collected at the end of the 1st half-shift and at the beginning of the 2nd half-shift in 5 workers. Results: In the foam production shop, TDI values were on average about 20 mg/m3, with higher levels in the 2nd half-shift and peak levels in workers operating along the polymerization tunnel. Average TDI levels were significantly correlated with ES TDA concentrations (p